Preoperative left hepatic lobe devascularisation to minimize perioperative bleeding in a Jehovah's Witness undergoing left hepatectomy. (2017) - Weinberg, Laurence; Hanus, Georgina; Banting, Jonathan; Abu-ssaydeh, Diana; Spanger, Manfred; Goh, Su Kah; Muralidharan, Vijayaragavan
Highlights: Liver resection in a Jehovah's Witness patient requires multimodal blood minimization strategies to improve patient centred outcomes. Combination portal vein embolization and hepatic lobe revascularization for total vascular inflow occlusion can allow a bloodless resection. Preoperative angio-embolization should be researched in a larger patient cohort to reduce blood loss and blood transfusion Abstract: Introduction: Major liver resection in a Jehovah's Witness presents unique clinical challenges requiring multimodal blood minimization strategies to reduce perioperative complications. We report a case where complete left hepatic lobe devascularisation was undertaken to minimize bleeding in a Jehovah's Witness undergoing left hepatectomy. Presentation of case: A 65-year-old male Jehovah's Witness presented for open left hepatectomy for a large left-sided hepatocellular carcinoma involving segment IV of the liver. Three weeks prior to surgery, the patient underwent left portal vein embolization. To isolate and devascularise the left lobe, the gastroduodenal artery and left hepatic artery were then occluded with coils. The bed of the left hepatic artery was then embolised to stasis with particles. Finally, the anastomosis back to the right hepatic artery was also occluded by coils. The patient underwent uneventful surgery with an estimated blood loss of 450 mls. Discussion: Left hepatectomy in a Jehovah's Witness patient is feasible but requires careful planning and a multidisciplinary approach. Major liver resection represents a well defined but complex haemostatic challenge from tissue and vascular injury, further complicated by hepatic dysfunction, and activation of inflammatory, haemostatic and fibrinolytic pathways. In addition to the haemoglobin optimization strategies utilized preoperatively, the use of interventional radiology techniques to further reduce perioperative bleeding should be considered in all complex cases. Conclusion: Combination of portal vein embolization and hepatic lobe devascularisation to produce total vascular occlusion of inflow to the left lobe radiologically allowed a near bloodless surgical field during major liver resection in a Jehovah's Witness patient.